(4,4'-H2bipy)4[Cu(4,4'-Hbipy)2(4,4'-bipy)(P2W18O62)2]·7H2O: A New Supramolecular Hybrid Based on 1D Cu-N Coordination Polymeric Chain and Wells-Dawson Type Polyoxometelate - Lin, Rui-Lian; Sun, Wen-Qi; Liu, Jing-Xin; Chu, Xiang-Feng (Asian Journal of Chemistry, 2015)
The hydrothermal reaction of CuCl2·2H2O with K6P2W18O62·15H2O and 4,4'-bipyridine (4,4'-bipy) gave a novel inorganic-organic hybrid (4,4'-H2bipy)4[Cu(4,4'-Hbipy)2(4,4'-bipy)(P2W18O62)2]·7H2O, in which Cu(II) coordinated to [P2W18O62]6- polyanions, 4,4'-bipydine and monoprotonated 4,4'-bipyridine ligands to form a 1D polyanionic chain. The 1D polyanionic chains stacked into a 3D supramolecular architecture consisting of numerous 1D open channels, in which water molecules are encapsulated. Additionally, thermal stability of the inorganic-organic hybrid materials has also been studied.